Analisis Semiotika pada Lirik Lagu O Tano Batak Karya Siddik Sitompul - Elsa Ria Saragih; Junifer Siregar; Vita Riahni Saragih (Journal on Education, 2023)
This research thesis is a study that aims to describe semiotics and describe icons, indexes and symbols in the lyrics of the song "O Tano Batak" by Siddik Sitompul. The type of this research is the method used in this research is a qualitative descriptive method by understanding the word that is the object of research. The results of this study include the Semiotics contained in the song "O Tano Batak" by Siddik Sitompul, namely icons, indexes, and symbols. The O Tano Batak song is a song originating from the North Sumatra region, especially the Batak tribal area. The lyrics of this song are presented to remind us of our hometown in Batak Land. Ancestral land, the land of origin of the Batak people. It is sung as a release of homesickness because the lyrics of this song are an expression of Batak youth who have migrated and longed for the atmosphere at home, namely in Batak Land.